1996
DOI: 10.1002/etc.5620150515
|View full text |Cite
|
Sign up to set email alerts
|

Selective assay for heavy metal toxicity using a fluorogenic substrate

Abstract: Chromogenic substrates have been generally used in enzymatic assays for the specific determination of heavy metal toxicity. A toxicity assay based on the specific inhibition of β‐galactosidase by heavy metals and using a fluorogenic substrate was evaluated for its sensitivity to heavy metals and organic toxicants. The toxicity assay, FluoroMetPLATE, was specific for heavy metals and was more sensitive than the widely used Microtox assay. Except for lead, our assay displayed sensitivity similar to that of the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This algae is unaffected by high ammonia concentrations and therefore is useful in TIE studies where bioassays using ammonia sensitive bioassays (e.g., sea urchin fertilization and embryological development) are used simultaneously. Whiteman et al (1996) (Jung et al 1996). The liquid assay was found to be specific for metals, more sensitive than Microtox ® , and similar to Ceriodaphnia dubia (48 hr acute assay) with the exception of Pb.…”
Section: Toxicity and Biomarker Testingmentioning
confidence: 85%
“…This algae is unaffected by high ammonia concentrations and therefore is useful in TIE studies where bioassays using ammonia sensitive bioassays (e.g., sea urchin fertilization and embryological development) are used simultaneously. Whiteman et al (1996) (Jung et al 1996). The liquid assay was found to be specific for metals, more sensitive than Microtox ® , and similar to Ceriodaphnia dubia (48 hr acute assay) with the exception of Pb.…”
Section: Toxicity and Biomarker Testingmentioning
confidence: 85%
“…Comparison of a 45-minute membrane response of N. obtusa cells with a 20-minute respiratory rate inhibition of bacterial blend (Polytox [9]), and 15-minute inhibition of bioluminescence of Vibrio fischeri (formerly known as Photobacterium phosphoreum; Microtox [9,10]) shows quite similar sensitivities toward the tested I).…”
Section: Reference Chemicalsmentioning
confidence: 94%
“…A concentration-dependent inhibition on the activity of the enzymegalactoside, has been proved for metals (Jung et al 1996;Apartin and Ronco 2001), complex mixtures (Babin et al 2001), and antimicrobials (Babin et al 2005. In our study, the toxic -galactosidase inhibition response (A, 2, and 6 samples) was always observed at concentrations producing dramatic effects on cell viability, and well correlated to the NR assay.…”
Section: Toxicological and Environmental Chemistry 233mentioning
confidence: 96%